2007
DOI: 10.1152/ajpgi.00406.2006
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes induces sex-dependent changes in neuronal nitric oxide synthase dimerization and function in the rat gastric antrum

Abstract: Gangula PRR, Maner WL, Micci M-A, Garfield RE, Pasricha PJ. Diabetes induces sex-dependent changes in neuronal nitric oxide synthase dimerization and function in the rat gastric antrum. Am J Physiol Gastrointest Liver Physiol 292: G725-G733, 2007; doi:10.1152/ajpgi.00406.2006.-Diabetic gastroparesis is a disorder that predominantly affects women. However, the biological basis of this sex bias remains completely unknown. In this study we tested the hypothesis that a component of this effect may be mediated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
151
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(158 citation statements)
references
References 55 publications
6
151
1
Order By: Relevance
“…There is a striking sex bias in gastroparetic patients, with women outnumbering men by a 4:1 ratio (18,19,34). Recent findings from our laboratory demonstrate that the reduction in gastric emptying is greater in female rats compared with males after diabetes induction (14). In addition, the study suggested that at least one biological reason for this sex bias may be differences in nitrergic regulation of gastric motility, with females being more vulnerable to changes in this system (14).…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…There is a striking sex bias in gastroparetic patients, with women outnumbering men by a 4:1 ratio (18,19,34). Recent findings from our laboratory demonstrate that the reduction in gastric emptying is greater in female rats compared with males after diabetes induction (14). In addition, the study suggested that at least one biological reason for this sex bias may be differences in nitrergic regulation of gastric motility, with females being more vulnerable to changes in this system (14).…”
mentioning
confidence: 66%
“…At the end of 3-wk BH4 supplementation, solid gastric emptying studies were performed as described previously (14). The rate of gastric emptying was calculated according to the following equation: gastric emptying (% in 4 h) ϭ (1 Ϫ gastric content/food intake) ϫ 100.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation is the fact that gastric emptying in female gender is on average slower than in males 12 . The other possible explanation is based on recent animal data which pointed that the effect of diabetes mellitus on the enteric nervous system is more expressed in females 14,15 .…”
Section: Diabetic Gastroparesismentioning
confidence: 99%